2006
DOI: 10.1111/j.1460-9568.2006.05204.x
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine exposure refines visual map topography through an NMDA receptor‐mediated pathway

Abstract: The precise mapping of one surface onto another is fundamental to visual system organization and depends upon adequate stimulation of postsynaptic targets to stabilize correctly placed synapses. As exogenous nicotine alters neuronal activity, we investigated whether it would affect the visual map created by retinal ganglion cell terminals in the frog optic tectum. Chronic exposure of the tectum to nicotine decreased the retinal area from which cells project to a given tectal site. This map refinement was also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 93 publications
(164 reference statements)
1
2
0
Order By: Relevance
“…This conclusion is further strengthened by the facts that this antibody recognizes an α7nAChR immunoreactive band of increasing density over time in primary cultures of rat hippocampal neurons (Arnaiz-Cot et al , 2008). In addition, the α7nAChR antibody used in our study has been shown to produce a similar pattern of labeling to α-bungarotoxin in the frog optic tectum (Yan et al, 2006) and the α7nAChR mRNA distribution and ligand binding in the rat central nervous system (Dominguez del Toro et al, 1994, Gotti and Clementi, 2004, Gotti et al, 2006). …”
Section: Discussionsupporting
confidence: 61%
“…This conclusion is further strengthened by the facts that this antibody recognizes an α7nAChR immunoreactive band of increasing density over time in primary cultures of rat hippocampal neurons (Arnaiz-Cot et al , 2008). In addition, the α7nAChR antibody used in our study has been shown to produce a similar pattern of labeling to α-bungarotoxin in the frog optic tectum (Yan et al, 2006) and the α7nAChR mRNA distribution and ligand binding in the rat central nervous system (Dominguez del Toro et al, 1994, Gotti and Clementi, 2004, Gotti et al, 2006). …”
Section: Discussionsupporting
confidence: 61%
“…Another intriguing possibility is raised by a recent report indicating that isthmic axons themselves are likely to have nicotinic presynaptic receptors (Yan,2006). Therefore, a positive feedback situation may arise once an isthmotectal axon forms a cluster of branches.…”
Section: Discussionmentioning
confidence: 99%
“…Each point of acetylcholine (ACh) release could potentially influence multiple retinotectal axons, and one can envision a situation in the which several isthmotectal branches or axons would have synergistic effects if they fired in a correlated manner in a localized tectal volume; the combined ACh generated by multiple nearby sources could easily have qualitatively different effects from the ACh generated by a single, isolated branch. This possibility is particularly likely in light of recent observations that isthmotectal axons themselves have acetylcholine receptors (Yan et al 2006). A cluster of isthmotectal axons with correlated activity might therefore create such a large pool of ACh that their terminals in turn would release additional ACh, in turn adding to the effect on the ACh receptors on the retinotectal terminals.…”
Section: Volume Versus Point Communicationmentioning
confidence: 99%